Synthesis, Photopolymerization, and Adhesive Properties of Hydrolytically Stable Phosphonic Acid-Containing (Meth)acrylamides - TÜRKER, ŞEBNEM BEGÜM (WILEY-BLACKWELL, 2014)
Three novel dental monomers containing phosphonic acid groups (1a and 2a, based on diethyl amino(phenyl)methylphosphonate and 3a based on diethyl 1-aminoheptylphosphonate) were synthesized in two steps: the reaction of -aminophosphonates with acryloyl chloride (for monomers 1a and 3a) or methacryloyl chloride (for 2a) to give monomers with phosphonate groups, and the hydrolysis of phosphonate groups by using trimethyl silylbromide. Their (and the intermediates') structures were confirmed by FTIR, H-1, C-13, and P-31 NMR spectroscopy. All the monomers dissolve well in water (1<pH<2) and are hydrolytically stable. Their homo- and copolymerizations with 2-hydroxyethyl methacrylate (HEMA) and HEMA/glycerol dimethacrylate were investigated with photo-DSC. Thermal polymerization of the new monomers in water or in ethanol/water solution was investigated, giving polymers in good yields. X-ray diffraction results showed only dicalcium phosphate dehydrate formation upon interaction of 1a-3a with hydroxyapatite indicating its strong decalcification and that monomer-Ca salts are highly soluble. Some results were also compared to those with a bisphosphonic acid-containing methacrylamide (4a) previously reported; and the influence of monomer structure on polymerization/adhesive properties is discussed. These properties, especially hydrolytic stability and good rates of polymerization, make these new monomers suitable candidates as components of dental adhesive mixtures. (c) 2013 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2014, 52, 511-522
Keywords: adhesives; dental polymers; hydrolytic stability; hydroxyapatite; photopolymerization; phosphonic acid; RADICAL POLYMERIZATION; DENTAL APPLICATIONS; MONOMERS; POLYMERS